Sistema RTP: uma técnica poderosa para o monitoramento da formação de nanotubos de carbono durante o processo por deposição de vapor químico - Juliana Cristina Tristão (2010)
In this work, a TPR (Temperature Programmed Reduction) system is used as a powerful tool to monitor carbon nanotubes production during CVD (Chemical Vapour Deposition), The experiments were carried out using catalyst precursors based on Fe-Mo supported on Al2O3 and methane as carbon source. As methane reacts on the Fe metal surface, carbon is deposited and H2 is produced. TPR is very sensitive to the presence of H2 and affords information on the temperature where catalyst is active to form different forms of carbon, the reaction kinetics, the catalyst deactivation and carbon yields.